Risk assessment for osteoradionecrosis of the jaws in patients with head and neck cancer - Acharya, Shruthi; Pai, Keerthilatha Murlidhar; Acharya, Shashidhar (Medicine and Pharmacy Reports, 2020)
Objectives. To identify the potential risk factors for the occurrence of osteoradionecrosis (ORN) of the jaws among patients who have been treated with radiotherapy for head and neck malignancy. Methods. The study comprised of 231 patients treated with radiotherapy for head and neck malignancy at a tertiary referral center. The following details were recorded for each patient: age, gender, histopathological diagnosis, clinical staging, tumor site, treatment modality, radiation dose, radiation field, number of fractions, type of accelerator used, radiation area and duration of follow-up . Patient’s tobacco, alcohol habit history, and history of extraction of teeth before/during/after radiotherapy were also noted. Results. Thirteen patients had osteoradionecrosis (frequency 5.62%). Among the radiotherapy variables assessed, increased radiation area was found to be significantly associated with the occurrence of osteoradionecrosis. Among the 13 ORN cases, 10 (76.9%) had a history of tobacco consumption, 8 (61.5%) had a time interval between radiotherapy and occurrence of ORN of less than 1-year duration. Discussion and conclusion. We found a low cumulative incidence of osteoradionecrosis and a tendency to occur within a year of starting radiotherapy. Patients of older age, those with a prior tobacco habit may be considered more liable to develop osteoradionecrosis. A larger radiation field may also put patients at hazard for developing osteoradionecrosis.